TK solver plus : Introduction to TK solver plus. (Illinois : Universal Technical Systems, Inc., 1989)
All the objects and their attributes can be entered (manually automatically) and are displayed and summarized on what are, in TK parlance, called sheets and subsheets.
Chapter 1. Tutorial -- Chapter 2. Commands -- Chapter 3. Sheets -- Chapter 4. Lists -- Chapter 5. Rule functions -- Chapter 6. Procedure functions -- Chapter 7. Logical computations -- Chapter 8. Complex variables.
Includes index.
Keywords: SHEETS -- COMPUTER